Innovative Environmental Protection Technologies to reduce Air Pollution from Cement Manufacturing Industry in Liberia - Gboe, Nuushuun Archie (Technium Sustainability, 2023)
The cement industry is a significant source of air pollution that has traditionally caused a great deal of public concern. Residents of Billima, Cow Factory, and Doe towns along the Japanese Freeway formerly Somalia Drive in Monrovia Liberia have continuously complained about air pollution in their neighborhoods as a result of the Cemenco cement production factory, which is the country’s largest cement manufacturing plant. Furthermore, there have been long-running disputes concerning air pollution from the Cemenco cement production complex and its potentially detrimental impacts on health and the environment. This paper presents an analysis of the cement manufacturing process, an outline of the pollutants generated from cement manufacturing plants, and the effects of these pollutants on human health and the environment. Finally, the research evaluates various non-technical pollution reduction strategies (emission control directives), innovative environmental protection technologies, and technological equipment to reduce pollution from the cement manufacturing industry.